The Bakhtin Reader - Helen Reid Thomas (Ilha do Desterro)
The publication of Caryl Emerson’s book The First Hundred Years of Mikhail Bakhtin in December 1997 is an indication that interest in Bakhtin continues to flourish, among both Russian and Western scholars. Emerson’s book traces the interesting differences of attitude and emphasis between these two groups of critics and provides a broad-ranging and scholarly history of Bakhtin studies. The book I am concerned with here, The Bakhtin Reader, though of a different nature and designed for a different audience, is perhaps an even more significant testament to Bakhtin’s extraordinary and continuing influence.